2008
DOI: 10.1021/ja806655f
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Terminal Gallylene Complexes by Halide Abstraction: Coordination Chemistry of a Valence Isoelectronic Analogue of CO and N2

Abstract: While N(2) and CO have played central roles in developing models of electronic structure, and their interactions with transition metals have been widely investigated, the valence isoelectronic diatomic molecules EX (E = group 13 element, X = group 17 element) have yet to be isolated under ambient conditions, either as the "free" molecule or as a ligand in a simple metal complex. As part of a program designed to address this deficiency, together with wider issues of the chemistry of cationic systems [L(n)M(ER)]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
43
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 79 publications
6
43
0
Order By: Relevance
“…Recently, a structurally characterized dimethylgallyl iridium complex [(Me)Ir(Me3GaCl)(GaMe 2 )(PCy 3 ) 2 ] has been reported by Merino and coworkers [24]. Fischer [27,29]. A number of theoretical studies of the terminal metal gallyl complexes have been reported [5,30e35].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a structurally characterized dimethylgallyl iridium complex [(Me)Ir(Me3GaCl)(GaMe 2 )(PCy 3 ) 2 ] has been reported by Merino and coworkers [24]. Fischer [27,29]. A number of theoretical studies of the terminal metal gallyl complexes have been reported [5,30e35].…”
Section: Introductionmentioning
confidence: 99%
“…5) were formed [35]. These disubstituted species, isolated from the reaction of GaCl 2 (N{SiMe 3 } 2 )·THF and Na[Fe(Á-C 5 R 5 )(CO) 2 ], were formed irrespective of the reaction stoichiometry and conditions.…”
Section: Equationmentioning
confidence: 97%
“…These include (i) the impressively large [Ga 84 Br 2 (N{SiMe 3 } 2 ) 20 ] 4− ( [35]) [37], and it's oxidized analogue, [Ga 84 Br 2 (N{SiMe 3 } 2 ) 20 ] 3− ( [36]) [38], each consisting of 64 × "naked" Ga atoms, with a further 20 that are bonded to -N{SiMe 3 } 2 ligands; (ii) the dianionic cluster [Ga 22 (N{SiMe 3 } 2 ) 10 ] 2− ( [37]) [39], which contains a central Ga atom surrounded by 11 × Ga atoms, with 10 × Ga-N{SiMe 3 } 2 groups around the periphery; (iii) the bromo/amido anions [Ga 22 Br( -Br) 10 (N{SiMe 3 } 2 ) 10 ] 3− ( [38]) and [Ga 22 Br 2 ( -Br) 10 [40], both of which contain an icosahedral Ga 12 unit without a central Ga atom, which is surrounded by a further 10 × Ga atoms and (iv) the neutral cluster, Ga 23 (N{SiMe 3 } 2 ) 11 (40) [41], which also contains a central Ga 12 core but is surrounded by 11 × Ga-N{SiMe 3 } 2 groups.…”
Section: Equationmentioning
confidence: 99%
“…Recently, a structurally characterized dimethylgallyl iridium complex [(Me)Ir(Cl.GaMe 3 )(GaMe 2 )(PCy 3 ) 2 ] has been reported by Merino and coworkers [42]. Fischer [44,45,47]. Pandey and coworkers have investigated in detail the bonding situation in dihalogallyl complexes of Ni, Pd, Pt, Fe, Ru and Os [48,49].…”
Section: Introductionmentioning
confidence: 93%
“…Fe(GaI 2 )] [dppe ¼ 1,2-bis(diphenylphosphino)ethane][44,45]. In addition, Braunschweig et al recently isolated dibromogallyl and diiodogallyl complexes of platinum, trans-X(PCy 3 ) 2 Pt(GaX 2 ) (X ¼ Br, I), using an oxidative addition methodology[46].…”
mentioning
confidence: 99%